Immunogenicity of recombinant outer membrane protein (OmpW) of Pasteurella multocida serogroup B:2 in mouse model - MOHANTY, N N; YOGISHARADHYA, R; SHIVACHANDRA, S B (The Indian Journal of Animal Sciences, 2019)
Haemorrhagic septicaemia (HS) caused by Pasteurella multocida serogroup B:2, in cattle and buffalo especially in tropical regions of Asian and African countries, is known to possess several outer membrane proteins (OMPs) as virulent factors which are being targeted to evaluate their immunogenicity and protective efficacy as candidate antigens for vaccine. In the present study, ompW gene encoding for OmpW protein of P. multocida serogroup B:2 strain P52, an Indian HS vaccine strain, has been cloned and over-expressed in recombinant Escherichia coli. The recombinant OmpW fusion protein ( 37 kDa) including histidine tag was purified by affinity chromatography under denaturing condition and confirmed by Western blotting. Further, mice immunized with rOmpW (50Î¼g/ dose) along with FCA/FIA resulted in antigen specific IgG antibodies as well as subtypes (IgG1 and IgG2a). The study indicated the potential possibilities to use the rOmpW antigen in developing subunit vaccine for HS as well as other diseases caused by members of Pasteurellaceae.